Geschichte der Sprachenpolitik Kameruns, oder: der lange Weg nationaler Sprachen aus der Verbannung - Djomo, Esaïe (Stellenbosch Papers in Linguistics Plus, 2012)
A major characteristic of Cameroon’s language policy during the colonial era as well as during the first four decades of the postcolonial era, is discrimination against all indigenous Cameroonian languages. This began when German was introduced after the arrival of the first colonisers in 1844 and lasted until the end of the First World War, after which the policy was continued by the French (in eastern Cameroon) and the English colonial administrators (in western Cameroon). Even after Independence in 1960, this policy was perpetuated and defended, now by the Cameroonian government who fostered so-called "Official Bilingualism", a policy securing the development of French and English as languages of education, and of administration and general public use in the entire country. The first attempt to put an end to this aspect of colonial policy occurred in 1996. Since then, a lot has been done to overcome and correct the policy of banishment of local languages, so that the Cameroonian languages are now being introduced into the educational system. Keywords: Schlüsselbegriffe: Kamerun, Sprachenpolitik, Nationalsprachen, Sprachrehabilitation Cameroon, language policy, national languages, language revitalisation